A Comprehensive Literature Review on the Emerging Trends in Educational Research concerning E-learning - Loebis, Iin Almeina (PT. Riset Press International, 2024)
This research is a literature review study that intends to determine trends in the use of E-learning for education, The method used is a literature study method where researchers search literature from 2018 to 2023 from various articles that have been published and journals indexed by Scopus, Sinta, Wos, Ebsco, Copernicus and Google Scholar. The result of this study is that currently the use of learning media has changed which previously only used blog-based media and changed to Virtual reality and is currently most widely used as a learning media. This can make it easier for learners to visualize learning. The conclusion obtained is that the use of e-learning media can increase learning value and can facilitate the understanding of lessons. The trend that is changing today is to use Virtual reality-based learning media. Researchers hope that this article will have a significant impact on learning and teaching staff can use learning media that are currently trending. The use of Virtual reality learning media makes it easier for students to understand visual learning and in terms of cost can be more efficient.